8 - Multiple Determinants of Milk Production in Africa: The Example of the Diversity of Dairy Farming Systems in the Mbarara Area (Uganda): by Julien Chalimbaud - Alary, Véronique; Faye, Bernard (Africa Development, 2007)
In developing countries, animal products supply presents a major challenge in meeting the demand for the two next decades. Many researchers point out the necessity for a ‘reasoned intensification’, especially in agricultural areas, by integrating agriculture and livestock activities. But intensification only occurs on specific farms. How can one explain the different dairy developments or technical options between farms? An analysis of the diversity of dairy farming systems in Mbarara district (Uganda) has been conducted from a monthly cross- sectional survey of a sample of 22 farmers, identified from a large household survey (183 dairy producers). The multi-table factorial analysis allows a thorough review of the interactions and points out some causal relationships between the development of the dairy systems and the social and technical management of the whole farm. This analysis underlines the key factors of intensification such as genetic improvement or market opportunities; but also the degree of intensification which is well correlated to the stage of family development. If the livestock may reinforce different functions (security, consumption, cash flow) according to the farm type, the results show that all these functions exist for all the farm types, either in the pastoral or agricultural areas. So these results question the stereotypes built on the different livestock systems in Africa.